Do higher hospital reimbursement prices improve quality of care? - Martin Salm; Ansgar Wübker (RWI - Leibniz-Institut für Wirtschaftsforschung, 2018)
Does higher medical spending improve quality of care? We estimate the effect of changes in regulated reimbursement prices for hospitals on multiple dimensions of hospital quality, including mortality outcomes, surgical complications, process quality, and patient satisfaction. We exploit an exogenous variation in reimbursement prices between the years 2006 and 2010 based on a reform of hospital financing in Germany. We find that changes in reimbursement prices do not affect quality of care. This effect is precisely estimated, and we can rule out effect sizes that are large relative to the overall variation in quality indicators across hospitals. – – Verbessern höhere medizinische Ausgaben die Qualität der Versorgung? Wir schätzen den Effekt von Änderungen der Vergütung von Krankenhäuser auf unterschiedliche Dimensionen der Krankenhausqualität, einschließlich Sterblichkeitsraten, chirurgischen Komplikationen, Prozessqualität und Patientenzufriedenheit. Auf Grundlage einer Reform der Krankenhausfinanzierung in Deutschland, nutzen wir eine exogene Variation der Krankenhausvergütung zwischen den Jahren 2006 und 2010. Wir finden, dass Änderungen der Erstattungspreise die Qualität der Versorgung nicht beeinträchtigen. Dieser Effekt ist präzise geschätzt, und wir können Effektgrößen ausschließen, die im Verhältnis zur Gesamtvariation der Qualitätsindikatoren zwischen den Krankenhäusern groß sind.
Keywords: I11; H51; D22; 330; health care expenditures; hospital care; quality of care